2011
DOI: 10.1007/s00296-011-1805-2
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of fibrin networks in rheumatoid arthritis: a qualitative analysis

Abstract: Rheumatoid arthritis is a chronic inflammatory condition that affects mainly synovial joints and has an impact on approximately 1% of the Western population. The coagulation process is altered in this condition, and this is frequently complicated by thrombocytosis. Changes in fibrin morphology have been linked with inflammation, and this, in turn, plays an important role in thrombosis. Changes in the fibrin fiber formation cause the alterations observed in thrombus morphology. In the current study, the ultrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 14 publications
6
29
0
Order By: Relevance
“…A similar increase in clot matrix density and fine fiber formation was observed in PPP obtained from smokers as determined by scanning electron microscopy (SEM) [83]. Using PRP, Pretorius and colleagues demonstrated by SEM the formation of not just finer fibers, but also sheet-like matting of thrombus ultrastructure in the settings of smoking [84], type II diabetes mellitus [85] and rheumatoid arthritis [86]. Representative SEM figures of normal PRP and the preceding three conditions are represented (Fig.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Cosupporting
confidence: 56%
See 2 more Smart Citations
“…A similar increase in clot matrix density and fine fiber formation was observed in PPP obtained from smokers as determined by scanning electron microscopy (SEM) [83]. Using PRP, Pretorius and colleagues demonstrated by SEM the formation of not just finer fibers, but also sheet-like matting of thrombus ultrastructure in the settings of smoking [84], type II diabetes mellitus [85] and rheumatoid arthritis [86]. Representative SEM figures of normal PRP and the preceding three conditions are represented (Fig.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Cosupporting
confidence: 56%
“…Investigations of platelet poor plasma (PPP) or platelet rich plasma (PRP) obtained from samples exposed to CORM-2 [50], obtained from smokers [83,84], obtained from patients with type II diabetes mellitus [85], and rheumatoid arthritis [86] all display similar Nielsen et al 16 16 features that may be secondary to CO exposure compared to normal subject plasma.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Comentioning
confidence: 97%
See 1 more Smart Citation
“…HO-1 activity is also increased systemically in inflammatory disorders associated with thrombophilia, such as diabetes mellitus [21] and rheumatoid arthritis [22]. Critically, SEM-based investigations demonstrated that the fibrin matrix formed from blood obtained from individuals with diabetes mellitus [23] or rheumatoid arthritis [24] was very similar to that observed when normal blood was exposed to ferric chloride [2][3][4][5][6][7]. In a complementary fashion, using a viscoelastic methodology validated to detect carbon monoxide-mediated hypercoagulability in the setting of tobacco smoking [25], it was determined that a patient with a clotted ventricular assist device and hemolysis had carbon monoxide-mediated hypercoagulability, and upregulation of HO-1 was documented by increased carboxyhemoglobin concentrations [26].…”
Section: Introductionmentioning
confidence: 99%
“…As was shown in our previous study on rheumatoid arthritis, the same microenvironment is responsible for the transformation of the fibrin network from a regular net of fibrils in healthy subjects to an amorphous fibrin deposit [17]. It is possible that inflammatory cellular elements, caught by the transformed network of fibrin fibres, trigger the firm clot formation resistant to anti-thrombotic agents.…”
Section: Discussionmentioning
confidence: 82%